Towards a Theory of Life Satisfaction Accounting for Stability, Change and Volatility in 25-Year Life Trajectories in Germany - Bruce Headey; Ruud Muffels (Institute for the Study of Labor (IZA), 2016)
An adequate theory of Life Satisfaction (LS) needs to take account of both factors that tend to stabilise LS and those that change it. The most widely accepted theory in psychology – setpoint theory – focussed solely on stability. That theory is now regarded as inadequate since several national panel surveys show that substantial minorities of respondents have recorded large, long term changes in LS. In this paper we elaborate a revised theory of LS change, based on analysis of the LS trajectories of respondents in the German Socio-Economic Panel who reported their LS for 25 consecutive years in 1990-2014. The theory entails three sets of propositions in which we attempt to account for stability, change and also volatility. First, it is proposed that stability is primarily due to stable personality traits, and to parental influence on LS. Second, the propositions indicate that medium and long term change are due to differences and changes in personal values/life priorities and behavioural choices. Differences and changes in pro-social values, family values and materialistic values affect LS, as do behavioural choices relating to one's partner, physical exercise, social participation and networks, church attendance, and the balance between work and leisure. Medium term change is further reinforced by two-way causation – positive feedback loops – between behavioural choices, domain satisfactions and LS. Third, our propositions break new ground in seeking to explain inter-individual differences in the volatility/variability of LS over time; why some individuals display high volatility and others low, even though their mean level of LS may change little over 25 years.
Keywords: J01; I12; I31; 330; life satisfaction (LS) theory; trajectories of LS; set-point theory; medium and long term change; volatility of LS; German Socio-Economic Panel